PROMOSI KESEHATAN MEMPENGARUHI PENGETAHUAN SISWA SD NEGERI - Anita Pramawati; Novela Sari (YCMM, 2021)
The Soil Transmitted helminths (STH) infection in the world were still relatively high. Indonesia in 2011, prevalence in Sumatera reached 78% and is estimated more than 60% of elementary school children in Indonesia suffered STH infections. The lack of knowledge about personal hygiene, environment, as well as that wormy infection made children easily got infected.This study was aimed to determine the effect of health promotion of the knowledge of students in grade 1,2,3 in siswa sd negeri 006 sei jang kecamatan bukit bestari kota tanjungpinang. The study design was quasi-experimental (quasi experiment) with pretest-posttest design group to 69 students in Agustus 2018. Health promotion was done with the lecture method and gave some leflet. Data was analyzed in univariate and bivariate analysis using the McNemar test. The results showed that there was an increased in knowledge after doing the health promotion, the p value = 0.001. Based on these results it can be concluded that health promotion can increase student’s knowledge in the effort of preventing the STH infection.